1994
DOI: 10.1177/107110079401500201
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis of the First Metatarsal Head: Incidence in Distal Osteotomy Combined with Lateral Soft Tissue Release

Abstract: The incidence of avascular necrosis of the metatarsal head following distal first metatarsal osteotomy combined with adductor tendon release has not been documented in a large series of patients. Of 82 consecutive procedures in 64 patients performed between 1986 and 1988, 42 patients (58 procedures) were available for clinical and radiographic examination. Average follow-up was 2.5 years (range 1.0-4.2 years). There were 35 L-shaped and 23 chevron osteotomies which were combined with a lateral soft tissue rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 11 publications
2
30
1
Order By: Relevance
“…These data were supported by findings from magnetic resonance imaging studies (27,48). In contrast, other investigators have found no association between necrosis and wide soft tissue release during hallux valgus surgery (11,(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 76%
“…These data were supported by findings from magnetic resonance imaging studies (27,48). In contrast, other investigators have found no association between necrosis and wide soft tissue release during hallux valgus surgery (11,(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 76%
“…10 However, the indications for distal chevron osteotomy are said to be limited to a hallux valgus angle (HVA) < 30° and a firstsecond intermetatarsal angle (IMA) < 15°. [10][11][12][13] Several recent studies have demonstrated that distal chevron osteotomy in conjunction with a distal soft-tissue procedure could enhance the amount of correction, suggesting that this combination can be applied to more severe deformities with a successful outcome. [9][10][11][12][13][14][15][16] However, a risk associated with a distal chevron osteotomy is avascular necrosis of the metatarsal head, 5,17 and an osteotomy combined with a distal softtissue procedure might increase the incidence of avascular necrosis.…”
mentioning
confidence: 99%
“…[10][11][12][13] Several recent studies have demonstrated that distal chevron osteotomy in conjunction with a distal soft-tissue procedure could enhance the amount of correction, suggesting that this combination can be applied to more severe deformities with a successful outcome. [9][10][11][12][13][14][15][16] However, a risk associated with a distal chevron osteotomy is avascular necrosis of the metatarsal head, 5,17 and an osteotomy combined with a distal softtissue procedure might increase the incidence of avascular necrosis. 11,15 The purpose of the present study was to compare the clinical and radiological outcomes between proximal chevron and distal chevron osteotomy combined with a soft-tissue procedure in severe hallux valgus deformity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In nonunion, delayed union and avascular necrosis of the metatarsal head the surgical procedures for distal metatarsal osteotomy should be different. Preserving (Jahss 198 1, Mann andCoughlin 198 1, Mann 1982, Home et al 1984) or performing lateral soft-tissue release (Resch et al 1992, Peterson et al 1994) results in different indications concerning more effective and acceptable limits of metatarsus primus varus (Corless 1976, Johnson et al 1979). …”
Section: Discussionmentioning
confidence: 99%